Evaluasi Kecacatan Produk Air Minum Dalam Kemasan (AMDK) 200 mL Menggunakan Metode FMEA (Failure Mode Effect Analysis) - Mubarok, Khoirul; Kurniawan, Rudi; Riyana, Iis (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
PT. DALWA ANUGRAHHASANIAH, a company that produces Packaged Drinking Water (AMDK) using ozone technology, this company also produces various sizes of glasses, bottles, and uses two types of raw materials - mineral water and demineralized water. This study aims to ensure that the AMDK production process does not experience defects. In an effort to reduce product defects, the Failure Mode and Effect Analysis (FMEA) method is used. FMEA is a proactive risk management method used to identify potential failures in a system, design, process, or service before it reaches the consumer. The goal is to prevent failure, maintain product quality, and reduce associated costs. The Failure Mode and Effect Analysis (FMEA) method is detailed, focusing on identifying failure modes, effects, causes, severity, occurrence, detection, and risk prioritization. Successful FMEA implementation is defined by a 30%-50% reduction in the new RPN value compared to the initial RPN value.